Serum Level and Single-nucleotide Polymorphism (rs1927911) of Toll-like Receptor 4 Among Type 2 Diabetes Mellitus Iraqi Patients - Ali, Sura Qusay; Salloom, Dunya Fareed (Iraqi Journal of Science, 2026)
Toll-like receptor 4 (TLR4), a member of the TLR family, plays a key role in innate immunity. Type 2 diabetes mellitus (T2DM) is a chronic condition characterized by impaired insulin sensitivity and abnormal immune responses. This study aimed to examine the association of the TLR4 single-nucleotide polymorphism (SNP) rs1927911 with T2DM susceptibility and to evaluate the SNP's effect on TLR4 levels. The study included 60 T2DM patients and 40 healthy controls. Blood samples were collected for serum analysis and DNA extraction. TLR4 levels were significantly elevated in T2DM patients carrying the AG genotype compared to controls (0.48 ± 0.10 vs. 0.30 ± 0.02 ng/ml, p = 0.03). Conversely, the controls with AA and GG genotypes had significantly higher levels of TLR4 compared to the patients (0.50 ± 0.11 versus 0.32 ± 0.08 and 0.43 ± 0.08 versus 0.35 ± 0.03 ng/ml, respectively), T2DM risk factors include AA genotype with an elevated incidence of T2DM (OR = 4.1), GG genotype (OR = 1.04), and the A allele (OR = 1.42). However, the AG genotype was not considered a risk factor for T2DM (OR = 0.47, 95% CI: 0.21–1.06). In conclusion, the AA and GG genotypes and the A allele contribute to T2DM susceptibility, while the AG genotype influences TLR4 levels without significantly increasing disease risk.